70.6k views
3 votes
Hello please help me with this expand question 3(p+5)-3(p+2) and please simplify

User GPP
by
5.3k points

2 Answers

4 votes

Answer:

9

Explanation:

3(p+5)-3(p+2)

3 x p is 3p

3 x 5 is 15

so the first half of the sequence is 3p+15

then -3p x p is -3p and -3 + 2 is -3p + 6

so it is 3p + 15 - 3p + 6

3p-3p is nothing then +15 - 6 is 9

which then goes to 9

9

User Anubhav
by
5.8k points
4 votes

Answer:

Explanation:

3(p + 5) - 3(p+2) = 3*p + 3*5 + (-3)*p + (-3)*2

= 3p + 15 - 3p - 6 {Bring the like terms together}

= 3p - 3p + 15 - 6

= 0 + 9

= 9

User Michael Norgren
by
5.8k points